A Kannemeyeriiform (Synapsida: Dicynodontia) Occipital Plate from the Middle Triassic Upper Fremouw Formation of Antarctica. Issue 5 (1st December 2020) - Smith, Nathan D.; Makovicky, Peter J.; Sidor, Christian A.; Hammer, William R.
ABSTRACT: A kannemeyeriiform dicynodont is described on the basis of an occipital plate from the upper Fremouw Formation (Middle Triassic) Gordon Valley locality in the Beardmore Glacier region of Antarctica. The Antarctic specimen is comparable in size to Kannemeyeria simocephalus from the well-known Cynognathus Assemblage Zone of the Beaufort Group of South Africa, and represents the largest therapsid currently known from the upper Fremouw Formation. The presence of an occipital condyle with distinct contributions from the exoccipital and the basioccipital; a wide, tri-radiate occipital condyle; and a well-developed tympanic process of the paroccipital, which is situated below the level of the occipital condyle, represent a combination of character states hitherto unknown among Kannemeyeriiformes. Combined with the possible autapomorphic feature of slender, dorsoventrally elongate basal tubera, this may suggest the Antarctic specimen represents a new kannemeyeriiform taxon. This specimen represents the most complete, and only the fourth definitive, dicynodont specimen known from the upper Fremouw Formation, and the contradictory phylogenetic character data from these specimens adds support for the presence of multiple (at least two) kannemeyeriiform taxa within the upper Fremouw tetrapod assemblage. Taken together, these kannemeyeriiform specimens provide additional support for a correlation with the Cynognathus Assemblage Zone, particularly the Trirachodon - Kannemeyeria or Cricodon - Ufudocyclops subzones (= subzones B or C), as well as an Anisian or younger age for the upper Fremouw tetrapod fauna.